Short Enantioselective Formal Synthesis of (–)-Platencin - Defieber, Christian; Mohr, Justin T.; Grabovyi, Gennadii A.; Stoltz, Brian M. (Synthesis, 2018)
A short enantioselective formal synthesis of the antibiotic natural product platencin is reported. Key steps in the synthesis include enantioselective decarboxylation alkylation, aldehyde/olefin radical cyclization, and regioselective aldol cyclization.
Keywords: formal synthesis; palladium; enantioselective reactions; enantioconvergent synthesis; alkylation